Loss of FHIT function in lung cancer and preinvasive bronchial lesions. - Sozzi, G; Pastorino, U; Moiraghi, L; Tagliabue, E; Pezzella, F; Ghirelli, C; Tornielli, S; Sard, L; Huebner, K; Pierotti, M; Croce, C; Pilotti, S (1998)
We previously cloned and characterized the tumor suppressor gene FHIT (fragile histidine triad) at chromosome 3p14.2 and found that this gene is altered by deletions in human tumors, including lung cancer. To assess the frequency and specificity of inactivation and its relevance in a clinical setting, we have produced antibodies against the Fhit protein and studied its expression in a series of non-small cell lung cancers and normal bronchial mucosa and a spectrum of preinvasive lesions by immunohistochemistry. The data indicate that the loss of Fhit protein is the most frequent alteration in non-small cell lung cancer (73%) and precancerous lesions (93%), is significantly higher in the tumors of smokers (75%) than in those of nonsmokers (39%; P < 0.0005), and is an independent and more frequent event than p53 overexpression in tumors and precancerous lesions (73 versus 46%). The percentage of cases lacking Fhit expression was higher in the squamous type compared to adenocarcinoma (87 versus 57%; P < 0.00001), whereas other histotypes (large cell, mucoepidermal) showed an intermediate value (69%). Loss of Fhit expression in a very high percentage of primary lung carcinomas and precancerous lesions supports the notion that FHIT alterations play an important role in the growth control of bronchial cells. FHIT inactivation is particularly important in squamous cell carcinomas that are often associated with precursor dysplastic lesions. The overall high frequency and precocity of Fhit loss in lung carcinogenesis and the development of the presently described immunohistochemical approach suggest a potential use of this gene in the early detection of lung cancer and in chemopreventive studies as an intermediate biomarker.